Research progress of sophoridine’s pharmacological activities and its molecular mechanism: an updated review - Chen, Yiwei; Wang, Xiang; Ye, Dongmei; Yang, Zhousheng; Shen, Qingrong; Liu, Xiaoxia; Chen, Chunxia; Chen, Xiaoyu (Frontiers in Pharmacology, 2023)
Background: Sophoridine, the major active constituent of Sophora alopecuroides and its roots, is a bioactive alkaloid with a wide range of pharmacological effects, including antitumor, anti-inflammatory, antiviral, antibacterial, analgesic, cardioprotective, and immunoprotective activities. Sophora flavescens Aiton is a traditional Chinese medicine that is bitter and cold. Additionally, it also exhibits the effects of clearing heat, eliminating dampness, and expelling insects. Aims of the study: To summarize the pharmacological research and associated mechanisms of sophoridine, we compiled this review by combining a huge body of relevant literature. Materials and methods: The information related to this article was systematically collected from the scientific literature databases including PubMed, Google Scholar, Web of Science, Science Direct, Springer, China National Knowledge Infrastructure, published books, PhD and MS dissertations. Results: Its antitumor activity is particularly remarkable, as it can inhibit cancer cell proliferation, invasion, and metastasis while inducing cell cycle arrest and apoptosis. Additionally, sophoridine also holds therapeutic potential for myocardial ischemia, osteoporosis, arrhythmias, and neurological disorders, primarily through the suppression of related inflammatory factors and cell apoptosis. However, sophoridine has also exhibited adverse effects such as hepatotoxicity and neurotoxicity. The antidisease effect and mechanism of sophoridine are diverse, so it has high research value. Conclusion: As an important traditional Chinese medicine alkaloid, modern pharmacological studies have demonstrated that sophoridine has prominent bioactivities, especially on anti-tumor anti-inflammation activities, and cardiovascular system protection. These activities provide prospects for novel drug development for cancer and some chronic diseases. Nevertheless, the understanding of the multitarget network pharmacology, long-term in vivo toxicity, and clinical efficacy of sophoridine require further detailed research.